Peraturan Adat: Studi Analisis Teori Receptio in Complexu dan Teori Receptio a Contrario - Zurifah Nurdin (JURNAL ILMIAH SYI'AR, 2016)
There are unwritten rules in society called customary law. The customary law sometimes conflict to the rules of religious. Moreover Muslim not to be involved in acts that are prohibited by the religion of Islam. The custom rules need to be analyzed through consideration of Islamic law which is a method of 'al-'Urf' by conducting to 'as-maslahah mursalah', so that the benefit of religion, life, property, descendent, and intellect maintained properly. This 'aqly' proposition is very useful for people who still impose customs rules that seemed to be obeyed. A good thing is not necessarily true yet according to Islam and the thruth is not conflict with the Qur'an and the Hadith of the Prophet as well as maqashid and asy-syari'ah.